2011
DOI: 10.1111/j.1600-0501.2011.02332.x
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar process preservation at implants installed immediately into extraction sockets using deproteinized bovine bone mineral – an experimental study in dogs

Abstract: The use of DBBM particles concomitantly with the application of a collagen membrane used at implants placed into sockets immediately after tooth extraction contributed to the preservation of the alveolar process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 36 publications
7
34
0
1
Order By: Relevance
“…At immediate implants, the reduction in both height and width was apparent in both implant groups. These findings are in agreement with other pre‐clinical investigations using similar image technology around immediate implants (Caneva et al., ). At delayed sites, in contrast, a gain in width was observed in both implant groups.…”
Section: Discussionsupporting
confidence: 93%
“…At immediate implants, the reduction in both height and width was apparent in both implant groups. These findings are in agreement with other pre‐clinical investigations using similar image technology around immediate implants (Caneva et al., ). At delayed sites, in contrast, a gain in width was observed in both implant groups.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with those from other reports on experimental studies on IPIES in dogs that have shown a limited improvement in bony crest preservation compared to untreated sites (Caneva et al. ; Favero et al. ).…”
Section: Discussionsupporting
confidence: 93%
“…The use of implants placed immediately into the extraction sockets (IPIES) has been shown to fail to prevent this resorption . Various attempts have been performed, aiming to preserve the alveolar ridge dimensions at IPIES sites that, however, only resulted in partial success …”
Section: Introductionmentioning
confidence: 99%